Cilia locally synthesize proteins to sustain their ultrastructure and functions - Kai Hao (Nature Portfolio, 2021)
Cilia are microtubule-based organelles containing proteins transported from the cell body. Here, the authors show that the multicilia of mouse ependymal cells contain ribosomal components, tubulin mRNA,18 S rRNA and nascent tubulin peptides, suggesting local translation in the ciliary compartment.